High-strength concrete containing mineral admixture and polymer composite fiber and preparation method thereof
By reacting polyvinyl alcohol and bialdehyde cellulose to form high-strength polyvinyl alcohol-cellulose gel, combined with stearic acid modified mineral powder, prepare polymer composite fibers and mineral blends and cement, and solve the problem of The problems of poor toughness and insufficient crack resistance of traditional concrete significantly improve the strength and durability of concrete.
Patent Information
- Application Number
- CN202410714165.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-06-04
AI Technical Summary
Traditional concrete has poor toughness, high brittleness, poor structural ductility and crack resistance, resulting in surface cracks, deep cracks and permeability temperature cracks in the early age, affecting the normal progress of construction. The existing fiber or mineral blends are There are problems such as poor dispersion performance, easy agglomeration, and large water demand in applications, making it difficult to effectively improve the strength and durability of concrete.
Polyvinyl alcohol and bialdehyde cellulose react to form high-strength polyvinyl alcohol-cellulose gel, and polymer composite fibers are prepared by melt spinning and thermal stretching, and mineral powders are modified by stearic acid to combine polymer composite The fiber and mineral blends are evenly mixed with cement, aggregate, etc. to form high-strength concrete.
The concrete's seepage resistance, tensile and split strength is improved, the crack development is inhibited, the compactness and mechanical properties of concrete are enhanced, and the early crack resistance and seepage resistance are significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a high-strength concrete containing mineral admixtures and polymer composite fibers and a preparation method thereof. Background Art
[0002] Concrete is the most widely used and largest-volume civil engineering material today. However, traditional concrete has some inherent defects, namely, poor toughness, high brittleness, poor structural ductility and crack resistance, and these defects become more significant as the strength of concrete increases. It not only reduces the mechanical properties and durability of concrete structures, but also incurs high maintenance costs. If not improved, early-stage concrete will develop surface cracks, deep cracks, and even penetrating temperature cracks, seriously affecting the normal progress of concrete construction. The addition of mineral admixtures or fibers can effectively improve its brittleness, making it a high-performance concrete with high strength and high toughness. Therefore, the development of a high-strength concrete containing mineral admixtures and polymer composite fibers has become a hot topic of current research.
[0003] Mineral micropowders are important mineral admixtures for concrete. Adding them to concrete can not only reduce the amount of cement used, but also realize the resource utilization of waste and improve the strength, durability and other aspects of concrete performance, ensuring the early strength and workability of concrete. However, adding only mineral admixtures will result in poor dispersion performance and easy agglomeration, which will reduce the slump and fluidity of concrete, and has a large demand for water, which is not conducive to engineering applications. In the existing technology, fibers are used to improve the performance of concrete, among which steel fibers have a large dosage, high cost, and are easy to rust, making them difficult to promote and apply in multiple fields. Synthetic fibers such as polypropylene and polyacrylonitrile have low bonding strength with concrete and cannot achieve the expected effect of crack resistance and enhancement. Carbon fiber has a high elastic modulus, a low ultimate elongation, and cannot be bent, limiting its scope of application.
[0004] Among organic fibers, polyvinyl alcohol fiber has gradually become a research hotspot as a concrete modification material due to its environmental protection, good hydrophilicity, good acid and alkali resistance, high bonding strength with cement stone and relatively low price. However, the elastic modulus of polyvinyl alcohol fiber is not as high as that of steel fiber, and the tensile strength is not as high as that of carbon fiber, and its dispersibility in concrete needs to be further improved. Cellulose fiber is also commonly used in concrete modification, but the negative Zeta potential of cellulose hinders its compatibility with cement, and it tends to agglomerate with each other, affecting the further improvement of concrete performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-strength concrete containing mineral admixtures and polymer composite fibers and a preparation method thereof, thereby solving the problems of low strength and poor impermeability and crack resistance of the prior art concrete.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A high-strength concrete containing mineral admixtures and polymer composite fibers comprises the following components in parts by weight: 350-500 parts of cement, 1000-1150 parts of coarse aggregate, 800-950 parts of fine aggregate, 100-200 parts of mineral admixtures, 160-190 parts of water, 2-5 parts of water reducing agent, 1-3 parts of anti-seepage agent, and 0.2-1 part of polymer composite fibers.
[0008] The preparation method of the polymer composite fiber is as follows:
[0009] (1) Add polyvinyl alcohol and water to a reaction flask, stir to dissolve, then drop hydrochloric acid to adjust the pH to 1.5-2.0, add dialdehyde cellulose, stir to react, and after the reaction is completed, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel.
[0010] (2) placing a high-strength polyvinyl alcohol-cellulose gel in a single-screw melt spinning machine for melt spinning, and obtaining spun fibers after melt extrusion and winding. The spun fibers are placed in a hot roller stretching device for heat stretching to obtain polymer composite fibers.
[0011] Preferably, the coarse aggregate is crushed stone with a particle size of 15-25 mm, and the fine aggregate is quartz sand with a particle size of 0.8-1.2 mm.
[0012] Preferably, the anti-seepage agent is any one of triethanolamine, calcium formate or urea.
[0013] Preferably, the preparation method of the mineral admixture is: add 1g of slag powder and 15-25mL of ethanol to a reaction flask, stir evenly, add 2.5-3.2g of stearic acid, react at 65-80°C for 1-3h, cool and filter, wash with ethanol, and dry to obtain the mineral admixture.
[0014] Preferably, the water reducer is any one of lignin sulfonate, melamine formaldehyde condensate or polycarboxylate water reducer.
[0015] Preferably, in step (1), the ratio of polyvinyl alcohol, water and dialdehyde cellulose is 1 g: (20-30) mL: (0.08-0.12) g.
[0016] Preferably, in step (1), the reaction temperature is 80-100° C. and the reaction time is 3-6 h.
[0017] Preferably, in step (2), the melt spinning temperature is 140-160°C, the spinning speed is 230-250 r / min; the heat stretching temperature is 180-210°C, the heat stretching rate is 35-50 mm / min, and the heat stretching multiple is 4-8.
[0018] Preferably, cement, coarse aggregate, fine aggregate and mineral admixture are mixed and added to a concrete mixer and dry mixed for 60-90 seconds. After mixing evenly, water and a water reducer are added and stirred for 3-5 minutes. The polymer composite fiber and an anti-seepage agent are added to the mixer and stirred for 10-20 minutes. After mixing evenly, the mixture is molded, vibrated and formed, cured and demolded to obtain a high-strength concrete containing mineral admixtures and polymer composite fibers.
[0019] By adopting the above technical solution, the beneficial effects of the present invention are:
[0020] The present invention firstly reacts polyvinyl alcohol with dialdehyded cellulose Schiff base to obtain high-strength polyvinyl alcohol-cellulose gel, then performs melt extrusion, winding and stretching to obtain polymer composite fibers, then uses stearic acid to perform surface modification on mineral micropowder to obtain mineral admixtures, and finally uniformly mixes the polymer composite fibers, mineral admixtures, cement, coarse and fine aggregates, water reducing agent, etc., and obtains high-strength concrete containing mineral admixtures and polymer composite fibers after curing and demolding.
[0021] The polymer composite fiber has a large specific surface area and a small fiber spacing. A large number of composite fibers can be evenly dispersed in the concrete to form a three-dimensional spatial network structure, which plays a role in supporting aggregates, reducing the pore channels in the concrete, thereby reducing the porosity of the concrete and improving the density of the concrete substrate. After the polymer composite fiber is added to the concrete, the effective bridging effect between the fiber and the concrete can share the complex shrinkage stress inside the matrix, thereby reducing the stress concentration at the crack tip, inhibiting the further development of the crack, preventing the penetration of micro cracks, and further improving the concrete's impermeability.
[0022] Polyvinyl alcohol fiber and cellulose fiber have complementary effects in inhibiting the development of concrete cracks at the macro and micro scales. After chemical reaction, the two fibers are cross-linked and entangled with each other, which can play a bridging role at different stages and scales of concrete crack development, making the interface transition zone of concrete denser. When subjected to external force, the fibers are evenly distributed inside the concrete to form a uniform, criss-crossed random support system, so that the microcracks formed in the early stage of hardening of the concrete are blocked in the process of development, reducing internal cracks and playing a role in blocking cracks.
[0023] After being modified with stearic acid, slag powder has good compatibility with concrete and good dispersibility in the concrete matrix, thereby better playing the role of "powder" and having a lubricating and dispersing effect on concrete, thereby further enhancing the mechanical properties of concrete; the synergistic effect of mineral admixtures and polymer composite fibers improves the tensile strength and splitting strength of concrete. DETAILED DESCRIPTION
[0024] The embodiments given below are for further explanation of the present invention, but should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above contents of the present invention still fall within the scope of protection of the present invention.
[0025] Preparation of dialdehyde cellulose: Add 1 g of alkalized nanocellulose and 50 mL of water to a brown reaction flask, stir evenly, adjust the pH to 2 with aqueous sulfuric acid solution, add 3.5 g of sodium periodate, react at 35 ° C in the dark for 3 h, cool to room temperature, add ethylene glycol, filter, wash with ethanol, and dry to obtain dialdehyde cellulose.
[0026] Example 1
[0027] (1) Add 15 g of polyvinyl alcohol and 225 mL of water to a reaction flask, stir to dissolve, then add hydrochloric acid dropwise to adjust the pH to 1.8, add 1.5 g of dialdehyde cellulose, react at 90 °C for 5 h, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel.
[0028] (2) High-strength polyvinyl alcohol-cellulose gel is placed in a single-screw melt spinning machine for melt spinning. The melt spinning temperature is 150°C and the spinning speed is 240 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching. The heat stretching temperature is 200°C, the heat stretching rate is 40 mm / min, and the heat stretching multiple is 5, thereby obtaining a polymer composite fiber.
[0029] (3) Add 10 g of slag powder and 200 mL of ethanol into a reaction flask, stir evenly, then add 28 g of stearic acid, react at 70 °C for 2 h, cool and filter, wash with ethanol, and dry to obtain a mineral admixture.
[0030] (4) 4500 g of cement, 11000 g of crushed stone with a particle size of 20 mm, 8500 g of quartz sand with a particle size of 0.9 mm and 1000 g of mineral admixture were mixed and added to a concrete mixer and dry mixed for 80 s. After mixing evenly, 1800 g of water and 30 g of lignin sulfonate water reducer were added and stirred for 4 min. 2 g of polymer composite fiber and 20 g of triethanolamine were added to the mixer and stirred for 15 min. After mixing evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0031] Example 2
[0032] (1) Add 35 g of polyvinyl alcohol and 700 mL of water to a reaction flask, stir to dissolve, then add hydrochloric acid dropwise to adjust the pH to 1.5, add 2.8 g of dialdehyde cellulose, react at 100 °C for 3 h, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel.
[0033] (2) The high-strength polyvinyl alcohol-cellulose gel is placed in a single-screw melt spinning machine for melt spinning. The melt spinning temperature is 160°C and the spinning speed is 250 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching. The heat stretching temperature is 210°C, the heat stretching rate is 50 mm / min, and the heat stretching multiple is 8, thereby obtaining a polymer composite fiber.
[0034] (3) Add 25 g of slag powder and 375 mL of ethanol into a reaction flask, stir evenly, then add 62.5 g of stearic acid, react at 80 °C for 1 h, cool and filter, wash with ethanol, and dry to obtain a mineral admixture.
[0035] (4) 3500 g of cement, 11500 g of crushed stone with a particle size of 15 mm, 9500 g of quartz sand with a particle size of 0.8 mm and 1000 g of mineral admixture were mixed and added to a concrete mixer and dry mixed for 90 s. After mixing evenly, 1600 g of water and 50 g of melamine formaldehyde condensation polymer water reducer were added and stirred for 5 min. 4 g of polymer composite fiber and 30 g of calcium formate were added to the mixer and stirred for 20 min. After mixing evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0036] Example 3
[0037] (1) Add 12 g of polyvinyl alcohol and 360 mL of water to a reaction flask, stir to dissolve, then add hydrochloric acid dropwise to adjust the pH to 1.5, add 1.44 g of dialdehyde cellulose, react at 80 °C for 6 h, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel.
[0038] (2) The high-strength polyvinyl alcohol-cellulose gel is placed in a single-screw melt spinning machine for melt spinning. The melt spinning temperature is 140°C and the spinning speed is 230 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching. The heat stretching temperature is 180°C, the heat stretching rate is 35 mm / min, and the heat stretching multiple is 4, thereby obtaining a polymer composite fiber.
[0039] (3) Add 5 g of slag powder and 125 mL of ethanol into a reaction flask, stir evenly, then add 16 g of stearic acid, react at 65 °C for 3 h, cool and filter, wash with ethanol, and dry to obtain a mineral admixture.
[0040] (4) 5000 g of cement, 10000 g of crushed stone with a particle size of 15 mm, 8000 g of quartz sand with a particle size of 0.8 mm and 1000 g of mineral admixture were mixed and added to a concrete mixer and dry mixed for 60 s. After mixing evenly, 1900 g of water and 20 g of polycarboxylate water reducer were added and stirred for 3 min. 6 g of polymer composite fiber and 30 g of urea were added to the mixer and stirred for 10 min. After mixing evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0041] Example 4
[0042] (1) Add 20 g of polyvinyl alcohol and 450 mL of water to a reaction flask, stir to dissolve, then add hydrochloric acid dropwise to adjust the pH to 1.6, add 2.2 g of dialdehyde cellulose, react at 95 °C for 4 h, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel.
[0043] (2) High-strength polyvinyl alcohol-cellulose gel is placed in a single-screw melt spinning machine for melt spinning. The melt spinning temperature is 155°C and the spinning speed is 245 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching. The heat stretching temperature is 190°C, the heat stretching rate is 45 mm / min, and the heat stretching multiple is 7, thereby obtaining a polymer composite fiber.
[0044] (3) Add 16 g of slag powder and 250 mL of ethanol into a reaction flask, stir evenly, then add 45 g of stearic acid, react at 75 °C for 3 h, cool and filter, wash with ethanol, and dry to obtain a mineral admixture.
[0045] (4) 4000 g of cement, 10500 g of crushed stone with a particle size of 20 mm, 8800 g of quartz sand with a particle size of 1 mm, and 1000 g of mineral admixture were mixed and added to a concrete mixer and dry-mixed for 80 s. After mixing evenly, 1800 g of water and 30 g of lignin sulfonate water reducer were added and stirred for 5 min. 8 g of polymer composite fiber and 20 g of triethanolamine were added to the mixer and stirred for 15 min. After mixing evenly, the mixture was molded, vibrated, cured, and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0046] Example 5
[0047] (1) Add 25 g of polyvinyl alcohol and 600 mL of water to a reaction flask, stir to dissolve, then add hydrochloric acid dropwise to adjust the pH to 1.8, add 3 g of dialdehyde cellulose, react at 95 °C for 5 h, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel.
[0048] (2) High-strength polyvinyl alcohol-cellulose gel is placed in a single-screw melt spinning machine for melt spinning. The melt spinning temperature is 150°C and the spinning speed is 245 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching. The heat stretching temperature is 205°C, the heat stretching rate is 40 mm / min, and the heat stretching multiple is 6, thereby obtaining a polymer composite fiber.
[0049] (3) Add 20 g of slag powder and 360 mL of ethanol into a reaction flask, stir evenly, then add 60 g of stearic acid, react at 80 °C for 2 h, cool and filter, wash with ethanol, and dry to obtain a mineral admixture.
[0050] (4) 4800 g of cement, 10200 g of crushed stone with a particle size of 25 mm, 9000 g of quartz sand with a particle size of 1.1 mm, and 1000 g of mineral admixture were mixed and added to a concrete mixer and dry-mixed for 70 s. After mixing evenly, 1800 g of water and 40 g of polycarboxylate water reducer were added and stirred for 5 min. 10 g of polymer composite fiber and 30 g of calcium formate were added to the mixer and stirred for 15 min. After mixing evenly, the mixture was molded, vibrated, cured, and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0051] Comparative Example 1
[0052] (1) Polyvinyl alcohol is placed in a single-screw melt spinning machine for melt spinning. The melt spinning temperature is 150°C and the spinning speed is 240 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching. The heat stretching temperature is 200°C, the heat stretching rate is 40 mm / min, and the heat stretching multiple is 5, thereby obtaining polyvinyl alcohol fibers.
[0053] (2) 4500 g of cement, 11000 g of crushed stone with a particle size of 20 mm, 8500 g of quartz sand with a particle size of 0.9 mm and 1000 g of mineral admixture (prepared in Example 1) were mixed and added to a concrete mixer and dry-mixed for 80 s. After mixing evenly, 1800 g of water and 30 g of lignin sulfonate water reducer were added and stirred for 4 min. 2 g of polyvinyl alcohol fiber and 20 g of triethanolamine were added to the mixer and stirred for 15 min. After mixing evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain concrete containing mineral admixture and polyvinyl alcohol fiber.
[0054] Comparative Example 2
[0055] (1) Cellulose is placed in a single-screw melt spinning machine for melt spinning at a temperature of 150°C and a spinning speed of 240 r / min. After melt extrusion and winding, spun fibers are obtained. The spun fibers are placed in a hot roller stretching device for heat stretching at a temperature of 200°C, a heat stretching rate of 40 mm / min, and a heat stretching multiple of 5 to obtain cellulose fibers.
[0056] (2) 4500 g of cement, 11000 g of crushed stone with a particle size of 20 mm, 8500 g of quartz sand with a particle size of 0.9 mm and 1000 g of mineral admixture (prepared in Example 1) were mixed and added to a concrete mixer and dry-mixed for 80 s. After mixing evenly, 1800 g of water and 30 g of lignin sulfonate water reducer were added and stirred for 4 min. 2 g of cellulose fiber and 20 g of triethanolamine were added to the mixer and stirred for 15 min. After mixing evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain concrete containing mineral admixture and cellulose fiber.
[0057] Comparative Example 3
[0058] 4500g of cement, 11000g of crushed stone with a particle size of 20mm, 8500g of quartz sand with a particle size of 0.9mm and 1000g of mineral admixture (prepared in Example 1) were mixed and added to a concrete mixer and dry mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 4min. 1g of cellulose fiber, 1g of polyvinyl alcohol fiber and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain concrete containing mineral admixtures and composite fibers.
[0059] Comparative Example 4
[0060] 4500g of cement, 11000g of crushed stone with a particle size of 20mm, 8500g of quartz sand with a particle size of 0.9mm and 1000g of mineral admixture (prepared in Example 1) were mixed and added to a concrete mixer and dry mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 4min. 20g of triethanolamine was added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain concrete containing mineral admixtures.
[0061] Early crack resistance test: According to "ASTM C 1579 Standard Test Method for Evaluation of Plastic Shrinkage Cracking of Fiber Concrete under Constrained State", the prepared concrete is poured into the mold, vibrated and smoothed, and then placed in an environment with wind direction parallel to the specimen surface, wind speed of 5m / s, temperature of 20℃, relative humidity of 60%, and illuminated by a 1kW bulb 30cm above the specimen surface. The time when the first crack appears on each specimen is recorded, which is recorded as the initial crack time; after 5h of treatment, the number of all cracks is carefully observed, and the maximum length and maximum width of the crack are measured with a reading microscope with an accuracy of 0.02mm.
[0062] Table 1 Early crack resistance test
[0063]
[0064] According to the test results in the above table, with the increase of polymer composite fiber content, the number of cracks, maximum crack width and maximum crack length of high-strength concrete gradually decreased, and the time for the first crack to appear gradually became longer, indicating that the addition of polymer composite fibers gradually enhanced the early crack resistance of concrete. This is because the polymer composite fibers contain two types of fibers, polyvinyl alcohol and cellulose, which have different elastic moduli and scales. The composite fibers after chemical grafting constitute a dense whole with good compatibility. They can play a bridging role at different stages and scales of concrete crack development, making the interface transition zone of concrete denser. When subjected to external force, the fibers are evenly distributed inside the concrete to form a uniform, criss-crossed random support system, so that the microcracks formed in the early stage of hardening of the concrete are blocked during the development process, reducing the germination of cracks and inhibiting the formation of through cracks, preventing the segregation of concrete, reducing internal cracks, and playing a role in blocking cracks.
[0065] Comparative Example 1 is concrete with only polyvinyl alcohol fiber, and Comparative Example 2 is concrete with only cellulose fiber. Both have poor early crack resistance because the effect of a single fiber in the concrete matrix is limited and there is a problem of easy agglomeration; Comparative Example 3 is concrete doped with polyvinyl alcohol fiber and cellulose fiber, but there is no chemical grafting between the two, only a simple physical blending, poor dispersion performance, and easy to produce stress concentration points; Comparative Example 4 does not add any fiber, and its early crack resistance is the worst.
[0066] Anti-seepage performance test: The prepared concrete is made into a truncated cone with a top diameter of 180 mm, a bottom diameter of 190 mm, and a height of 150 mm, and tested according to the seepage height method of the "Test Code for Hydraulic Concrete" (SL 352-2020).
[0067] Table 2 Anti-seepage performance test
[0068]
[0069] According to the test results in the above table, as the content of polymer composite fibers increases, the anti-permeability performance of high-strength concrete gradually increases. The maximum water seepage height in Example 4 is 46.30 mm, and the maximum permeability coefficient is 1.56×10 -10 cm / s, which significantly increases the anti-seepage ability of concrete. This is because, on the one hand, the polymer composite fiber has a large specific surface area and a small fiber spacing. A large number of composite fibers are evenly dispersed in the concrete to form a three-dimensional spatial network structure, which plays a role in supporting aggregates, reducing the pore channels in the concrete, thereby reducing the porosity of the concrete, improving the density of the concrete substrate, reducing the water loss area of the concrete matrix and making it difficult for water to migrate; on the other hand, after the polymer composite fiber is added to the concrete, the effective bridging effect between the fiber and the concrete can share the complex shrinkage stress inside the matrix, thereby reducing the stress concentration at the crack tip, inhibiting the further development of the crack, preventing the penetration of fine cracks, and further improving the anti-seepage performance.
[0070] Example 6
[0071] 4000g of cement, 10500g of crushed stone with a particle size of 20mm, 8800g of quartz sand with a particle size of 1mm and 1250g of mineral admixture were mixed and added to a concrete mixer and dry-mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 5min. 8g of polymer composite fiber (prepared in Example 4) and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0072] Example 7
[0073] 4000g of cement, 10500g of crushed stone with a particle size of 20mm, 8800g of quartz sand with a particle size of 1mm and 1500g of mineral admixture were mixed and added to a concrete mixer and dry mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 5min. 8g of polymer composite fiber (prepared in Example 4) and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated into shape, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0074] Example 8
[0075] 4000g of cement, 10500g of crushed stone with a particle size of 20mm, 8800g of quartz sand with a particle size of 1mm and 1750g of mineral admixture were mixed and added to a concrete mixer and dry mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 5min. 8g of polymer composite fiber (prepared in Example 4) and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated and formed, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0076] Example 9
[0077] 4000g of cement, 10500g of crushed stone with a particle size of 20mm, 8800g of quartz sand with a particle size of 1mm and 2000g of mineral admixture were mixed and added to a concrete mixer and dry mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 5min. 8g of polymer composite fiber (prepared in Example 4) and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated to form, cured and demolded to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.
[0078] Comparative Example 5
[0079] 4000g of cement, 10500g of crushed stone with a particle size of 20mm, 8800g of quartz sand with a particle size of 1mm and 1000g of slag powder were mixed and added to a concrete mixer and dry-mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 5min. 8g of polymer composite fiber (prepared in Example 4) and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain a high-strength concrete containing mineral admixtures and polymer composite fibers.
[0080] Comparative Example 6
[0081] 4000g of cement, 10500g of crushed stone with a particle size of 20mm, and 8800g of quartz sand with a particle size of 1mm were mixed and added to a concrete mixer and dry-mixed for 80s. After mixing evenly, 1800g of water and 30g of lignin sulfonate water reducer were added and stirred for 5min. 8g of polymer composite fiber (prepared in Example 4) and 20g of triethanolamine were added to the mixer and stirred for 15min. After stirring evenly, the mixture was molded, vibrated and molded, cured and demolded to obtain high-strength concrete with polymer composite fibers.
[0082] Compressive strength test: The test was carried out in accordance with the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T 50081-2019). The prepared concrete was made into specimens of 100mm×100mm×100mm, cured for 7 days under standard conditions, and its compressive strength and splitting strength were tested.
[0083] Table 3 Concrete mechanical properties test
[0084]
[0085] According to the test results in the above table, with the increase of the content of mineral admixtures, the mechanical properties of concrete are gradually enhanced. The compressive strength in Example 8 reaches 48.9 MPa, and the splitting strength reaches 4.23 MPa. This is because the slag powder has good compatibility with concrete after being modified with stearic acid, and has good dispersibility in the concrete matrix, thereby better playing the role of "powder", which has a lubricating and dispersing effect on the concrete, and further enhances the mechanical properties of the concrete; Comparative Example 5 adds slag powder, which is not modified with stearic acid, resulting in poor dispersibility in the concrete matrix, easy agglomeration, and cannot play a good reinforcing role of the mineral admixture.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength concrete containing mineral admixtures and polymer composite fibers, characterized in that: The high-strength concrete is composed of the following components in parts by weight: 350-500 parts of cement, 1000-1150 parts of coarse aggregate, 800-950 parts of fine aggregate, 100-200 parts of mineral admixture, 160-190 parts of water, 2-5 parts of water reducing agent and 1-3 parts of anti-seepage agent, and 0.2-1 parts of polymer composite fiber; The preparation method of the polymer composite fiber is: (1) Add polyvinyl alcohol and water to a reaction flask, stir to dissolve, then drop hydrochloric acid to adjust the pH to 1.5-2.0, add dialdehyde cellulose, stir to react, and after the reaction is completed, add sodium hydroxide to adjust the solution to neutral, filter, and wash with ice water to obtain a high-strength polyvinyl alcohol-cellulose gel; (2) placing the high-strength polyvinyl alcohol-cellulose gel in a single-screw melt spinning machine for melt spinning, and obtaining spun fibers after melt extrusion and winding. The spun fibers are placed in a hot roller stretching device for heat stretching to obtain polymer composite fibers; In step (1), the ratio of polyvinyl alcohol, water and dialdehyde cellulose is 1 g: (20-30) mL: (0.08-0.12) g; In step (2), the melt spinning temperature is 140-160°C, the spinning speed is 230-250 r / min; the heat stretching temperature is 180-210°C, the heat stretching rate is 35-50 mm / min, and the heat stretching multiple is 4-8; The coarse aggregate is crushed stone with a particle size of 15-25 mm, and the fine aggregate is quartz sand with a particle size of 0.8-1.2 mm; The preparation method of the mineral admixture is as follows: add 1g of slag powder and 15-25mL of ethanol into a reaction flask, stir evenly, add 2.5-3.2g of stearic acid, react at 65-80°C for 1-3h, cool and filter, wash with ethanol, and dry to obtain the mineral admixture.
2. The high-strength concrete containing mineral admixtures and polymer composite fibers according to claim 1, characterized in that: The anti-seepage agent is any one of triethanolamine, calcium formate or urea.
3. The high-strength concrete containing mineral admixtures and polymer composite fibers according to claim 1, characterized in that: The water reducer is any one of lignin sulfonate, melamine formaldehyde condensate or polycarboxylate water reducer.
4. The high-strength concrete containing mineral admixtures and polymer composite fibers according to claim 1, characterized in that: In the step (1), the reaction temperature is 80-100° C. and the reaction time is 3-6 hours.
5. A method for preparing high-strength concrete containing mineral admixtures and polymer composite fibers as claimed in any one of claims 1 to 4, characterized in that: Mix cement, coarse aggregate, fine aggregate and mineral admixture, add them into a concrete mixer and dry mix for 60-90 seconds. After mixing evenly, add water and water reducing agent and stir for 3-5 minutes. Add polymer composite fiber and anti-seepage agent into the mixer and stir for 10-20 minutes. After mixing evenly, fill the mold, vibrate to form, cure and demould to obtain high-strength concrete containing mineral admixtures and polymer composite fibers.